Rancang Bangun Sistem Informasi Akademik Berbasis Web Pada Universitas Nahdlatul Ulama Sidoarjo - Ibnu Muslim; Anjik Sukmaaji; Arifin Puji Widodo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
University of Nahdlatul Ulama Sidoarjo (UNSIDA) is a new college in Sidoarjo who has the vision to improve UNU Sidoarjo as Higher Education Excellence and Competitive in the development of science, technology and art. in UNSIDA, system that handle administrative process is already exist using Excel but considering inadequate. There is a lack of evaluation report every month to rector, dean and kaprodi to process data for purpose of measuring the performance of academic activity within certain period.  that will becomes no synergy and integration on each department. there are also other problem where the students and parents caused by lack of communication between university with parents. As result, parents are often missinformed about the academic activity progress.Therefore, to solve these problems, there is a need to build an Academic Information System that manage information of students. The Academic Information System must be capable of producing usefull reports about academic activities as university performance for dean. The system must also capable of providing schedule for lecturer and student. Keywords: academic, information system, evaluation report